Varietal improvement and agronomy research in Malaysia - Tan, Swee Lian (International Center for Tropical Agriculture, 1998)
Over the period 1994-1996, seven batches of seeds and two of meristem tissue cultures were evaluated and selected. As important as root yield is the trait starch content (or dry matter content) if a clone is to be accepted as a starch cultivar. At the time of reporting a number of clones have been identified as having yield levels similar to the high-yielding early cultivar MM 92, while showing dry matter contents equivalent to that of the commercial starch cultivar Black Twig. Two of these promising clones have also been evaluated positively for processing into oil fried crisps, a popular local snack.